High resolution computed tomography in chronic obstructive pulmonary disease - D., Pragati Rao; Talatam, Aruna; B., Chakradhar; K., Bhargavi; A., Bhagyaraj (International Journal of Advances in Medicine, 2018)
Background: Chronic obstructive pulmonary disease (COPD) is a common preventable and treatable disease characterised by persistent respiratory symptoms and airflow limitation with varied presentations (bronchitis and emphysema). High resolution computed tomography (HRCT) plays an important role in identifying the various morphologies thereby reducing morbidity and mortality. The aim of the present study was to evaluate the role of high resolution computed tomography in COPD patients. The Objectives of the present study was to differentiate emphysema predominant, airway predominant and mixed phenotypes and to identify other disease processes and complications. Methods: 50 COPD patients attending Respiratory medicine Department, NRI general hospital were advised for chest x-rays and pulmonary function tests. All the patients selected were smokers with no other co-morbid illnesses. Those patients whose chest x-rays showed no other changes except for COPD changes were selected for HRCT chest. Results: Out of 50 COPD patients emphysema predominance was present in 28 patients (56%), bronchitis predominance in 19 patients (38%) and 3(6%) patients had mixed pattern. In emphysema centriacinar pattern was commonly seen (42.9%), paraseptal in 35.71%, panacinar in 3.57% and bullae in 17.8% cases. All the patients were chronic smokers with pack years >20. All are males with average age above 45 years. Emphysema was common in elderly patients with age above 50 years. Chronic bronchitis is predominantly seen in the age group 40-50 years. Additional diagnoses like bronchiectasis, mass, ILD were identified in 28% cases. Conclusions: HRCT plays a significant role in COPD patients in differentiating phenotypes which have different modes of therapy. Other subtle changes in lungs which cannot be identified on chest x ray are discernible on HRCT. Early identification of complications reduces morbidity and mortality.